Celecoxib Blocks Vasculogenic Mimicry via an Off-Target Effect to Radiosensitize Lung Cancer Cells: An Experimental Study - Niu, Kai; Chen, Xie-Wan; Qin, Yu; Zhang, Lu-Ping; Liao, Rong-Xia; Sun, Jian-Guo (Frontiers in Oncology, 2021)
The resistance to radiotherapy in lung cancer can be attributed to vasculogenic mimicry (VM) to some extent. Celecoxib (CXB), a selective inhibitor of cyclooxygenase-2 (COX-2), is reported as a radiosensitizer in non-small cell lung cancer (NSCLC). However, whether CXB can regulate VM formation via an off-target effect to radiosensitize NSCLC remains unclear. This study aimed to elucidate the mechanism underlying the radiosensitizing effect of CXB on NSCLC i.e. whether CXB can inhibit VM formation via binding to newly identified targets other than COX-2. CXB radiosensitivity assay was performed in the control, CXB, irradiation (IR) treatment, and IR plus CXB groups. In vitro VM formation was observed using 3D matrigel and periodic acid solution (PAS) staining. COX-2 inhibition by CXB was detected in cell lines and xenografts with or without IR treatment. The potential off-targets of CXB other than COX-2 were screened using PDB database, MGLTools 1.5.6 and Autodock_vina 1.1.2, and confirmed by western blotting, enzyme activity assay and RNA interference in vitro experiments, and by immunohistochemistry, PAS staining and VM formation in vivo experiments. CXB radiosensitivity assay was performed in BALB/c mice bearing H460 xenografts and C57 mice bearing Lewis lung cancer (LLC) xenografts. CXB treatment almost eliminated VM formation enhanced by IR in vitro and in vivo, partially due to COX-2 inhibition. By bioinformatics analysis, four potential targets other than COX-2 were predicted for further verification. Among them, aminopeptidase N (APN) and integrin alpha-V (ITAV) were remarkably inhibited in protein expression and enzyme activity in vitro or in vivo, consistent with the remarkable reduction of VM formation in H460 xenografts in BALB/c mice. In conclusion, CXB dramatically blocked vasculogenic mimicry through inhibiting newly identified off-targets ITAV and APN, other than COX-2, thus radiosensitizing NSCLC.